2013
DOI: 10.1007/s00497-013-0222-y
|View full text |Cite
|
Sign up to set email alerts
|

Apomixis in plant reproduction: a novel perspective on an old dilemma

Abstract: Seed is one of the key factors of crop productivity. Therefore, a comprehension of the mechanisms underlying seed formation in cultivated plants is crucial for the quantitative and qualitative progress of agricultural production. In angiosperms, two pathways of reproduction through seed exist: sexual or amphimictic, and asexual or apomictic; the former is largely exploited by seed companies for breeding new varieties, whereas the latter is receiving continuously increasing attention from both scientific and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
146
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(149 citation statements)
references
References 163 publications
(198 reference statements)
2
146
0
1
Order By: Relevance
“…APOSTART may also be related to programmed cell death and the degeneration of the nonfunctional megaspores, with one of the two isolated copies (APOSTART1) overexpressed in sexual lines relative to apomicts. The Arabidopsis APOSTART1 ortholog is expressed in mature female embryo sacs and developing embryos, and the phenotype of APOSTART1/APOSTART2 double mutants suggests that this gene has a role in embryo and seed development (Barcaccia and Albertini 2013).…”
Section: Differentially Expressed Genes Associated With Apomixismentioning
confidence: 99%
“…APOSTART may also be related to programmed cell death and the degeneration of the nonfunctional megaspores, with one of the two isolated copies (APOSTART1) overexpressed in sexual lines relative to apomicts. The Arabidopsis APOSTART1 ortholog is expressed in mature female embryo sacs and developing embryos, and the phenotype of APOSTART1/APOSTART2 double mutants suggests that this gene has a role in embryo and seed development (Barcaccia and Albertini 2013).…”
Section: Differentially Expressed Genes Associated With Apomixismentioning
confidence: 99%
“…In gametophytic apomixis, a chromosomally unreduced embryo sac develops from the megaspore mother cell (diplospory) or from a nearby nucellar cell (apospory) in a process termed apomeiosis. Parthenogenesis, the development of the unreduced, unfertilized egg into an embryo, constitutes the second step of the apomictic process (1,2).…”
mentioning
confidence: 99%
“…In wheat, the alloplasmic line 'Salmon' with the 1BL/1RS chromosome in its genome is a suitable material for parthenogenesis research (Barcaccia and Albertini 2013;Curtis and Grossniklaus 2008). It has been reported that the short arm of chromosome 1B from common wheat (Triticum aestivum L.) is substituted by the short arm of chromosome 1R from rye (Secale cereale L.) in 'Salmon', thereby yielding 1BL/1RS translocation wheat.…”
Section: Introductionmentioning
confidence: 99%